Risk Factors for Predicting Lymph Nodes Posterior to Right Recurrent Laryngeal Nerve (LN-prRLN) Metastasis in Thyroid Papillary Carcinoma: A Meta-Analysis - Cunfu Li; Jun Xiang; Yunjun Wang (International Journal of Endocrinology)
Objective. To evaluate the risk factors for predicting lymph nodes (LN) posterior to right recurrent laryngeal nerve metastasis in thyroid papillary carcinoma. Methods. PubMed, PMC, EMBASE, and the Cochrane Library were systematically searched for articles published spanning 30/06/2009-30/8/2018 using multiple search terms. Thirteen articles involving 10,014 patients were reviewed in our meta-analysis. Stata 15.1 software was used for the meta-analysis. Results. The rate of LN posterior to right recurrent laryngeal nerve (LN-prRLN) metastasis was 8.65%. Univariate analysis showed that age (P=0.001), gender (P<0.001), tumour size (P<0.001), lateral LN metastasis (P<0.001), extrathyroidal invasion (P<0.001), multifocality (P=0.005), capsule invasion (P<0.001), tumour location (P=0.076), lymph nodes anterior to right recurrent laryngeal nerve (LN-arRLN) metastasis (P<0.001), and central LN metastasis (P<0.001) were significantly associated with the increased incidence of LN-prRLN metastasis in thyroid papillary carcinoma. Conclusion. PTC patients aged <45, male, and with tumours>1 cm, lateral LN metastasis, extrathyroidal invasion, multifocality, capsule invasion, LN-arRLN metastasis, or central LN metastasis were significantly correlated with lymph nodes posterior to right recurrent laryngeal nerve metastasis, indicating LN-prRLN dissection.